A cationic [Ag12S12] cluster-based 2D coordination polymer and its dye composite with enhanced photocurrent and dielectric responses. Issue 24 (28th May 2019) - Zhang, Min; Tan, Yu-Ling; Chen, Xu-Ran; Yu, Hong; Zhang, Wen-Hua; Lang, Jian-Ping
Abstract : A cationic cluster-based 2D coordination polymer captures Congo Red to form a composite with improved photocurrent and dielectric responses. Abstract : A cationic two-dimensional coordination polymer sustained by a [Ag12 S12 ] cluster secondary building unit has been prepared from a stepwise solid-state reaction. This coordination polymer is capable of associating the anionic dye Congo Red, yielding a composite material that exhibits improved photocurrent and dielectric responses as compared to the pristine polymer.